The Effectiveness Of Fire Safety Measures Of Government Hospital Buildings In Johor, Malaysia - Othman, Jamil Hj. Abdullah @ (2023)
Hospital has been designed to function in emergency services and ongoing patient treatment. However, some operations in hospital facilities can expose the hospital and its residents, including personnel and patients, to the plausibility of unexpected fire threats. Like most hospitals worldwide, building complexity has been an issue for safe evacuation during a fire. A fire at Sultanah Aminah Hospital in Johor Bahru, Johor, Malaysia, in 2016 demonstrated that fire could destroy buildings and property and cause injury and death. Therefore, it is imperative to see the extent of the perception of staff working in hospitals about the effectiveness of fire safety measures in government hospital buildings in Johor, Malaysia. In this study, two main groups of hospital services (clinical and non-clinical) are stratified based on service norms into three groups: management staff, medical staff, and engineering/technical staff, including Medivest Sdn. Bhd. as a Hospital Support Service. The study aims to expose the connection between the effectiveness of fire safety measures of government hospital buildings in Johor, Malaysia, regarding building occupancy, layout, and building usage in 12 hospital buildings in Johor, Malaysia.